Digenic Origin of Difference of Sex Development in a Patient Harbouring DHX37 and MAMLD1 Variants - Katia Margiotti; Francesco Libotte; Marco Fabiani; Alvaro Mesoraca; Claudio Giorlandino (Case Reports in Pediatrics)
Background. The diagnostic process for identifying variations in sex development (DSD) remains challenging due to the limited availability of evidence pertaining to the association between phenotype and genotype. DSD incidence is reported as 2 in 10,000 births, and the etiology has been attributed to genetic causes. Case Presentation. The present study investigated genetic causes implicated in a case of a 15-year-old 46, XY patient, raised as a girl. Genetic analysis by clinical exome sequencing (CES) showed a digenic inheritance due to two known pathogenic mutations in the DHX37 gene and the MAMLD1 gene, while we excluded variants with pathogenic significance in 209 DSD-related genes. Conclusions. Based on our literature review, this is the first case with the combined presence of pathogenic mutations in the MAMLD1 gene and DHX37 gene in a patient with gonadal dysgenesis.